Effect of ground water level on the release of carbon, nitrogen and phosphorus during decomposition of Carex. cinerascens Kükenth in the typical seasonal floodplain in dry season. Issue 1 (1st January 2019) - Zhang, Quanjun; Zhang, Guangshuai; Yu, Xiubo; Liu, Yu; Xia, Shaoxia; Ya, Li; Hu, Binhua; Wan, Songxian
Abstract: From November 2016 to April 2017, the decomposition of Carex. cinerascens Kükenth litter along the natural gradients of groundwater level at Poyang Lake wetland beach were simulated using litterbag technique. The depth of the underground water table of the G-L was −25 to −50 cm, while those of G-ML, G-MH and G-H ranged from −15 to −25 cm, −5 to −15 cm, and −5 to 5, respectively. Additionally, the dry weight loss rate increased gradually with increasing days, with that of G-H being highest, followed by G-MH, G-ML and G-L. The decomposition rate of the four gradients increased rapidly to day 30, then decreased slowly until stabilizing. Additionally, the decomposition rate was highest in G-H, followed by G-MH, G-ML and G-L. The Olson negative exponential model could simulate the decomposition good and predicted the time required for 50% decomposition of the G-H, G-MH, G-ML and G-L gradients was about 166, 197, 205 and 247 days, respectively, while required for 95% was about 1.97, 2.23, 2.43 and 2.92 years, respectively. The overall trend in the relative return index of carbon, nitrogen and phosphorus increased with increasing decomposition days, and the order was G-H > G-MH > G-ML > G-L. Differences in soil pH, bulk density, soil total nitrogen, soil organic matter, microbial biomass carbon and soil sand content in the decomposed environment due to groundwater had a significant impact on decomposition and nutrient release. The relative return index of carbon was significantly positively correlated with soil pH, but significantly negatively correlated with soil bulk density, soil nitrogen content, microbial biomass nitrogen and soil organic matter. The above results show that groundwater is the key factor influencing litter decomposition in Poyang Lake wetland during the dry season, with higher groundwater levels promoting the decomposition.